Analysis of Phrases Based on their Forming Elements in the Film Langit Tak Selamanya Abu-Abu by Kemendikbud RI - Marshanda, Tirza; Hidayatul, Alina; Rindu, Jihanita; Jannah, Miftahul; Oxana, Oktian; Pratama, Rakha; Aisy, Rihada; Salamah, Siti; Rumboy, Yuliva; Suhita, Raheni (Lingua Franca, 2024)
The purpose of this study is to analyze the film "Langit Tak Selamanya Abu-Abu " based on its constituent elements on the sentence structure contained in the film's dialogue. This type and approach of research is qualitative/library research. The research data in this study is a phrase based on its constituent elements, while the source of the data is the film Langit Tak Forever Abu Karya Kemendikbud RI. Data collection techniques using documentation and data analysis techniques using content analysis The results of the study showed, in every dialogue delivered by the characters in the film " Langit Tak Selamanya Abu-Abu " which has a duration of 8 minutes 31 seconds, an analysis of Phrases based on their Constituent Elements can be found, namely 1) Endocentric Phrases, namely phrases that have distribution similarities with their constituent elements, in the film contains only 1 endocentric phrase, namely Attributive Endocentric Phrases, 2) Exocentric Phrases, which are phrases that have no distribution equation with other elements, in the film there are 2 exocentric phrases, namely Prepositional and Conjunctional Exocentric Phrases. Based on the results of the study, it can be concluded that the analysis of phrases in the film " Langit Tak Selamanya Abu-Abu " based on its constituent elements, namely, found 8 data with a total of 48 phrases, with 30 attributive endocentric phrases, 15 conjunctional exocentric phrases, and 3 prepositional exocentric phrases.